Android-Based Media Innovation to Improve Vocational Students’ Task Performance and Self-Regulated Learning - Feni Eka Damayanti; Madziatul Churiyah; Ardian Novianti (Transpublika Publisher, 2026)
The development of 21st-century digital technology calls for a transformation of learning media in vocational high schools to address students’ low levels of self-regulated learning and task performance in meeting administration practical training. This study aims to develop an Android-based learning medium called “Smart Meeting Admin” to improve task performance and self-regulated learning among vocational high school students majoring in Office Management and Business Services. The research method used is Research and Development (R&D) employing the ADDIE development model. Data were collected through expert validation sheets, student response questionnaires, and measurement instruments for task performance and self-regulated learning, analyzed descriptively and quantitatively. The results indicate that the “Smart Meeting Admin” platform is deemed highly suitable for use based on evaluations by subject matter experts and media experts. Additionally, there was a significant improvement in students’ self-regulated learning abilities and task performance scores after utilizing this application in the learning process. The implications of this study suggest that the integration of mobile-based learning media can serve as an effective innovative solution to foster independent learning while optimizing students’ practical skills in the digital age.